Pembangunan Kota Berkelanjutan: Studi Bibliometrik - Mahriadi, Nopriawan; Adiatma, Tini; Mita, Maichel Santo Wijaya (Jurnal Publisitas, 2023)
Sustainable urban development or so-called "urban sustainable development" is one of the research topics that has recently developed in the world recently due to an increase in public awareness of the importance of sustainability. This study aims to examine the development of publication trends related to urban sustainable development. This study uses a visual bibliometric analysis method with VOS Viewer. Publication data obtained from the ScienceDirect website shows an increase in the number of publications from 2013-2022. The study of urban sustainable development research articles is mostly related to cities, systems, effects, impacts, and factors. The number of publications related to cities is 420 research articles, 406 articles on systems, 355 research articles related to effects, 243 research articles related to impacts, and 222 research articles related to factors in sustainable development.